Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/nag.2321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of material point method for use in geotechnics

Abstract: SUMMARYThe first part of the paper presents a material point method solution for the bearing capacity of a deep foundation in purely cohesive soil, which is a widely known engineering problem. The results computed with the generalised interpolation material point method are compared to the results obtained previously with an advanced limit analysis code. The second part of the paper shows material point method simulations of collapsing piles of granular material and compares the results with experimental obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 33 publications
(81 reference statements)
2
59
0
2
Order By: Relevance
“…MPM can be seen as an ALE FEM in which all computational variables, including mass, are stored in every single material point. Its application to geotechnical engineering has been discussed and demonstrated by Solowski and Sloan [35]. Its ability to tackle fluid-like behaviours of granular material has been demonstrated by Wieckowski [42].…”
Section: Simulating the Column Collapsementioning
confidence: 99%
See 2 more Smart Citations
“…MPM can be seen as an ALE FEM in which all computational variables, including mass, are stored in every single material point. Its application to geotechnical engineering has been discussed and demonstrated by Solowski and Sloan [35]. Its ability to tackle fluid-like behaviours of granular material has been demonstrated by Wieckowski [42].…”
Section: Simulating the Column Collapsementioning
confidence: 99%
“…However, the SPH simulation required a large number of particles to obtain an accurate run-out distance making it computationally more expensive. Solowski and Sloan [34,35] compared MPM simulations with the experimental data of Lube et al [23] and showed that the Mohr-Coulomb model did not dissipate sufficient energy. Hence, the run-out distances were largely overestimated and numerical damping had to be applied in order to match the experimental results.…”
Section: Simulating the Column Collapsementioning
confidence: 99%
See 1 more Smart Citation
“…As the mass carried by each material point is assumed unchanged throughout the computation, the conservation of mass is implicitly satisfied. The motion and deformation are assumed to be governed by the momentum equations, and its weak form can be written as: Ωρbold-italica·δbold-italicvdbold-italicx+Ω𝛔:δbold-italicvdbold-italicx=Ωρbold-italicb·δbold-italicvdbold-italicx+normalΩ𝛕·δbold-italicvdS, where “·” denotes first‐order vector contraction, “:” represents second‐order tensor contraction, “∇” denotes the gradient operator, ρ is current mass density, a is the acceleration, δ v is an admissible velocity field, σ is the Cauchy stress, b is the body force, τ is the boundary traction, and Ω and ∂ Ω represent the entire current domain of continuum and its boundary, respectively.…”
Section: Hierarchical Coupling Of Mpm and Dem: Formulation And Methodmentioning
confidence: 99%
“…However, the aforementioned computational methods are restricted to the small strain range. If large deformation problems are to be solved, particle or meshfree methodologies arise as suitable alternatives for simulating such problems . The name of “meshfree methods” comes from the fact that they do not rely on meshes but on points to approximate functions and differential operators.…”
Section: Introductionmentioning
confidence: 99%